The procurement and supply manager's desk reference - Sollish, Fred (Wiley, 2012)
Every supply manager's essential desktop tool with in-depth, authoritative coverage of each topic Leaving no stone unturned in covering all aspects of the procurement and sourcing functions, The Procurement and Supply Manager's Desk Reference, Second Edition is filled with everything every organization needs to know about the key roles and responsibilities of a procurement professional. Presented logically to match the flow of the procurement and sourcing functions, the book is filled with practical aids such as step-by-step guides to each segment of the process, as well as checklists and cust.